PFAS exposure of humans, animals and the environment: Protocol of an evidence review map and bibliometric analysis. (January 2022) - Vendl, Catharina; Taylor, Matthew D.; Bräunig, Jennifer; Gibson, Matthew J.; Hesselson, Daniel; Gregory Neely, G.; Lagisz, Malgorzata; Nakagawa, Shinichi
Highlights: Exposure to PFAS is a major concern of public and environmental health. We present a protocol using the research weaving approach on PFAS review literature. Research weaving combines evidence review mapping and bibliometric analysis. This overview will include reviews on PFAS in humans, animals, and the environment. This review of reviews will inform and enhance relevant future research and policy. Abstract: Background: Per- and polyfluoroalkyl (PFAS) substances are a group of anthropogenic organic chemicals. PFAS have numerous applications in the industrial and commercial fields. They have become abundant in the environment and have been detected in the blood of humans and animals. PFAS exposure likely increases the risk of certain diseases. In recent years, there has been a steep rise in related primary and secondary articles. Objectives: We aim to collate narrative and systematic reviews including both qualitative and quantitative synthesis on biological, environmental, or medical aspects of PFAS exposure and burdens, and to create an evidence review map to fulfil three main objectives. 1) Mappingto reveal what evidence on PFAS has been systematically reviewed and where synthesis may be needed. 2) Bibliometrics: to characterise the interdisciplinarity, independence and connectedness of the reviews. 3) Critical appraisal: to assess the included reviews for the reliability of conclusions and methodological transparency. This overview of reviews will inform future research and policy making. Search and study eligibility: We will perform a systematic search on Scopus, Web of Science, PubMed, and the 'grey literature'. To be included in the map, a study must be a review from the systematic review family and focus on at least one of predefined 31 PFAS. We will limit inclusions to peer-reviewed publications, pre-prints, and theses without any language restrictions. At least two authors will scan title, abstract and keywords, followed by full-text screening of included reviews. Critical appraisal of reviews and synthesis methods: We will assess each review of the systematic review family referencing the AMSTAR2 checklist. We will collect information on conflict-of-interest statements, funding sources and availability of raw data and analysis code. We will extract relevant data from full texts and bibliographic records, conduct bibliometric analyses, and display findings as tables, figures and a narrative synopsis.